OPTIMALISASI PENGELOLAAN DOKUMEN DALAM MENINGKATKAN PELAYANAN CALON JEMAAH HAJI PADA KANTOR KEMENTERIAN AGAMA KOTA BUKITTINGGI - Romida Puspita Sari; Khadijah Nurani (Jurnal Ekonomi dan Bisnis, 2024)
This study is driven by issues with the method for managing Hajj registration documents as efficiently as possible, which are occasionally hindered by the network, and by prospective pilgrims' ignorance of the Hajj registration process, which frequently results in inaccuracies in congregational data. This study looks at how best to optimize document management systems as a service for potential Hajj travelers and how document management and services for potential Hajj travelers relate to each other. This study used qualitative research methods. The approach used in this research is a descriptive qualitative approach. The data used are primary data and secondary data, primary data was obtained from staff involved in the Hajj and Umrah Organizers of the Bukittinggi City Ministry of Religion, while secondary data was obtained by collecting data using observation, interviews and documentation methods. The research results obtained by the author show that the Bukittinggi City Ministry of Religion has managed Hajj documents effectively and efficiently according to Poerwadarminta's optimization theory. Document management is carried out well using an IT-based system in its management, and continues to make optimization efforts in managing Hajj documents so that Hajj document management services run optimally. And the management of Hajj documents is included in the services for Hajj pilgrims because in its implementation it applies services in the form of verbal, written and deeds which are applied very well by Hajj officers.